SUBJECTIVE SLEEP NEED AND DAYTIME SLEEPINESS IN ADOLESCENTS - Ferrari Junior,Geraldo Jose (2019)
ABSTRACT Objective: To analyze the contribution of subjective sleep need for daytime sleepiness in adolescents, and to compare questions about sleep, age and body mass index between adolescents who considered to sleep enough and those who reported the need for more sleep. Methods: This is a descriptive, epidemiological and cross-sectional study. Data collection was performed in August 2016, with 773 adolescents aged 14-19 years old, from Paranaguá, Paraná, Southern Brazil. The analysis included the following variables: time in bed, half-sleep phase, sleep need, social jetlag, daytime sleepiness, body mass index and physical activity. Results: The prevalence of adolescents with subjective need for sleep was 73.0%, with an average need of 1.7 extra hours of sleep. These adolescents woke up earlier (p<0.001) and slept less on school days (p<0.001). The need for more sleep was associated with higher daytime sleepiness scores (rho=0.480; p<0.001) and with later half-sleep phase (rho=0.200; p<0.001). No correlation was identified between the sleep need and time in bed (rho=-0.044; p=0.225). The subjective sleep need was the variable with the greatest explanatory power for daytime sleepiness (24.8%; p<0.001). In addition, the less adolescents practiced physical activity, the higher their daytime sleepiness scores (rho=-0.117; p<0.001). Conclusions: The subjective sleep need has an important role in explaining daytime sleepiness among adolescents. Adolescents who needed to sleep more reported waking up early and experienced sleep deprivation during class days; they also woke up later on the weekends and experienced more daytime sleepiness, compared to those who believed they had enough sleep.